Role of Interleukin-12 in Immune Response Polarization and Parasite Persistence in Cutaneous Leishmaniasis - Faris, Reham Firas (American Journal of Biology and Natural Sciences, 2026)
Cutaneous leishmaniasis is one of the parasitic diseases caused by Leishmania species and characterized by many symptoms, ranging from automatic lesion to chronic infection. Disease Development is mainly influenced by host–parasite interactions in addition to balance between cellular Immunological responses. The aim of current study is to examine the importance of interleukin-12 (IL-12) in regulating immune responses and its effect on parasite continuation in Subjects with cutaneous leishmaniasis. Total of 100 patients were grouped into three groups: individuals with self-healing, Chronic patients ,-healthy group as a control group. Levels of IL-12, interferon-gamma (IFN-γ), and interleukin-4 (IL-4) is serum were measured using ELISA, then statistical analyses were conducted using ANOVA then by Tukey’s post-hoc test for multiple comparisons. The results have shown that patients who spontaneous healing show significantly higher levels of IL-12 and IFN-γ compared to both chronic cases and healthy controls, indicating a strong T helper 1 (Th1)-mediated immune response associated with effective parasite clearance. In contrast, chronic patients showed high levels of IL-4, suggesting a biased T-helper 2 (Th2) immune response that may Enhance parasite survival within host macrophages. These results highlight the critical role of IL-12 in controlling host immune responses and affecting disease result in cutaneous leishmaniasis. From a parasitological perspective, IL-12 may Play a role in enhancing intracellular parasite clearance and could act as a possible immunological biomarker for disease progression.